2015
DOI: 10.1002/jcb.25046
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Zinc‐Finger Protein 777 (ZNF777) Inhibits Proliferation at Low Cell Density Through Down‐Regulation of FAM129A

Abstract: Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs) regulate a wide range of cellular processes. KRAB-ZFPs have a KRAB domain, which binds to transcriptional corepressors, and a zinc finger domain, which binds to DNA to activate or repress gene transcription. Here, we characterize ZNF777, a member of KRAB-ZFPs. We show that ZNF777 localizes to the nucleus and inducible overexpression of ZNF777 inhibits cell proliferation in a manner dependent on its zinc finger domain but independent of its KRAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…A recent study by Yuki et al . showed that overexpression of a zinc‐finger protein (ZNF777) inhibited proliferation of cells at low density through down‐regulation of FAM129A (Niban) 18. This finding and our finding that there is striking up‐regulated expression of BCNP1 on stimulation of LD ALL3 cells by HDSN of HD ALL3 cells strongly suggests that BCNP1 might have an important role in cell density‐dependent cell proliferation at least in B‐cells.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…A recent study by Yuki et al . showed that overexpression of a zinc‐finger protein (ZNF777) inhibited proliferation of cells at low density through down‐regulation of FAM129A (Niban) 18. This finding and our finding that there is striking up‐regulated expression of BCNP1 on stimulation of LD ALL3 cells by HDSN of HD ALL3 cells strongly suggests that BCNP1 might have an important role in cell density‐dependent cell proliferation at least in B‐cells.…”
Section: Introductionsupporting
confidence: 63%
“…Given the relative frequency of BCNP1 alterations in many cancer types warrant further investigation of its function providing answers to question when BCNP1 is amplified, deleted or mutated. Our recent observation that BCNP1 (FAM129C) was the most highly up-regulated gene when non-growing low density Ph+ ALL3 cells were stimulated to proliferate by cell-free supernate from the same cells growing rapidly at a high cell density, and Yuki's report that overexpression of ZNF777 inhibited proliferation of cells at low density by down-regulating FAM129A, suggests that BCNP1 probably has a very important role in cell-cell communication and corresponding intracellular signalling pathways [16,17,18].…”
Section: Fig 7 P38mentioning
confidence: 99%
See 1 more Smart Citation
“…4, A and B), both myc-Ku70 and myc-Ku70/sh R constructs were acceptable for transfection into HeLa S3/shKu70 cells. pEBmulti/puro/myc-Ku70-WT or its mutant was constructed as follows: the XhoI and NotI sites were created at the both ends of pcDNA3/myc-Ku70 by PCR with 5Ј-GTCACTCGAGATGGAGCAGAAACTCATCTCT-GAAGAGG-3Ј (sense) and 5Ј-TCATGCGGCCGCTCAGTC-CTGGAAGTGCTTGG-3Ј (antisense), and the XhoI-NotI fragment of the PCR product was subcloned into the episomal pEBmulti/puro vector (Wako Pure Chemical Industries) (73). Intact c-Src and HA-tagged c-Src (c-Src-HA) were constructed from cDNA encoding human wild-type Src (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The EBNA1-based episomal pEBMulti-H1 vector, which encodes the H1 promoter and a neomycin-resistant gene, was generated from the pEBMulti vector (Wako Pure Chemical Industries, Osaka, Japan) by replacing the CAG promoter with the H1 promoter as described (37). The oligonucleotides used for shRNA were annealed and subcloned into the pEBMulti-H1 vector (37)(38)(39). To generate AKAP8-knockdown cells, HCT116 cells were transfected with pEBMulti-neo/shAKAP8 selected in 600 g/ml G418.…”
Section: Methodsmentioning
confidence: 99%